Dari Identitas Politik ke Politisasi Identitas: Kajian Konseptual atas Dinamika Polarisasi di Media Sosial - Febri Saefulloh; Agung Tesa Gumilar; Titi Alawiyah; kartika Delsya; Ria Erica Salty (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Identity politics has become one of the most debated concepts in contemporary democratic discourse, yet its conceptual boundaries remain poorly defined in both academic and public conversations. This paper argues that three commonly conflated terms political identity, identity politics, and the politicization of identity carry fundamentally distinct meanings with divergent normative and practical consequences. Through a conceptual literature review, this study synthesizes theoretical frameworks and empirical findings to demonstrate that while political identity refers to an individual's self-positioning within a political community, and identity politics denotes collective action by marginalized groups seeking recognition, the politicization of identity is an elite-driven strategy of exploiting social group markers for political gain. This distinction matters because the conflation of these terms obscures how digital platforms through filter bubble and echo chamber mechanisms amplify identity-based polarization in Indonesia and beyond. The study finds that social media algorithms do not merely reflect pre-existing social divisions but actively intensify affective polarization by constructing homogeneous information environments that deepen inter-group animosity. The paper concludes with implications for digital citizenship and democratic resilience in Indonesia.